IT governance enablers for an efficient IoT implementation - Henriques, David Rodrigues (2020)
IoT is considered to be one of the focal points for the 4.0 industry revolution because of the way it is changing the business models of each organization. IT governance is now an increasingly important tool for organizations to align their IT infrastructure with the organization's business objectives. IT governance has been used to help implement new technologies using the best practices such as COBIT, which defines a number of enablers that facilitate the implementation, identification and management of IT. This research aims to explore and define the most suitable enablers for an IoT implementation. These objectives will be achieved through the Design Science Research methodology, which incorporates two literature reviews, a Delphi method and, finally, a semi-structured interview. With a first systematic review of the literature, it was possible to identify the main enablers to implement IoT. Next, the list was improved using the Delphi method, gathering expert opinion. In the Delphi method, the level of agreement was verified to create exclusion criteria and a level of efficiency in each recommendation. Finally, a specialist was interviewed to demonstrate the applicability and validation of the proposed artifact in the various IoT projects implemented by his organization. At the end, a final list of enablers for IoT implementation is provided. The results indicate that data privacy, data protection, and data analysis are currently the best recommendations to be considered in an IoT implementation because they increase the efficiency of the solution and increase the credibility of the data obtained. Future work and limitations are detailed in the end.